2020
DOI: 10.1021/acscentsci.0c00604
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Dispersed Iridium on Indium Tin Oxide Efficiently Catalyzes Water Oxidation

Abstract: Heterogeneous catalysts in the form of atomically dispersed metals on a support provide the most efficient utilization of the active component, which is especially important for scarce and expensive late transition metals. These catalysts also enable unique opportunities to understand reaction pathways through detailed spectroscopic and computational studies. Here, we demonstrate that atomically dispersed iridium sites on indium tin oxide prepared via surface organometallic chemistry display exemplary catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 70 publications
3
54
0
Order By: Relevance
“…[79][80][81][82] In 2020, an in situ XAS study observing the oxidation state of atomically dispersed iridium oxide on indium tin oxide (ITO) in 0.1 M HClO 4 during the OER was reported by Lebedev et al 79 They measured in situ XANES at Ir L III -edge at 1.46 V vs. RHE and assigned an Ir-O distance of 1.83 ± 0.02 Å as an Ir +5 vO intermediate, which was the predominant species under OER conditions. 79 Subsequently, the same authors further investigated the reaction mechanism by DFT calculation and suggested the formation of the Ir +6 dioxo intermediate after the formation of the Ir +5 vO intermediate. 79 This result of the formation of Ir +5 vO is consistent with the observations on the heterogeneous solid states as discussed in this review.…”
Section: Spectroscopic Evidence To Support the Claimed Catalytic Cyclmentioning
confidence: 99%
See 1 more Smart Citation
“…[79][80][81][82] In 2020, an in situ XAS study observing the oxidation state of atomically dispersed iridium oxide on indium tin oxide (ITO) in 0.1 M HClO 4 during the OER was reported by Lebedev et al 79 They measured in situ XANES at Ir L III -edge at 1.46 V vs. RHE and assigned an Ir-O distance of 1.83 ± 0.02 Å as an Ir +5 vO intermediate, which was the predominant species under OER conditions. 79 Subsequently, the same authors further investigated the reaction mechanism by DFT calculation and suggested the formation of the Ir +6 dioxo intermediate after the formation of the Ir +5 vO intermediate. 79 This result of the formation of Ir +5 vO is consistent with the observations on the heterogeneous solid states as discussed in this review.…”
Section: Spectroscopic Evidence To Support the Claimed Catalytic Cyclmentioning
confidence: 99%
“…79 Subsequently, the same authors further investigated the reaction mechanism by DFT calculation and suggested the formation of the Ir +6 dioxo intermediate after the formation of the Ir +5 vO intermediate. 79 This result of the formation of Ir +5 vO is consistent with the observations on the heterogeneous solid states as discussed in this review. 67 This type of study would cultivate a better understanding of OER catalysis from a comprehensive perspective, and furthermore would eventually bridge the gap between heterogeneous and homogeneous catalysis.…”
Section: Spectroscopic Evidence To Support the Claimed Catalytic Cyclmentioning
confidence: 99%
“…Noteworthily, in some flexible systems such as oxidized iridium surfaces or supported dimeric Ir species the I2M mechanism has been suggested to be competitive with the WNA one. 47,48,54 Taking WNA as the applying mechanism, three different rate determining steps have been proposed depending on the material, level of theory and subtle differences in the nature of the elementary steps: i) The Ir=O formation (B to C step in Scheme 1); ii) the electrochemical step associated with the Ir-OOH formation (C to E step in Scheme 1) and iii) O2 release from Ir-OOH (E to A in Scheme 1). Controversy persists, and one can find recent contributions suggesting that either the formation of Ir-OOH or the O2 release are the rate determining processes.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] In general, catalysts based on noble metals, like iridium and ruthenium, [8,[15][16][17] exhibit better performances than the earthabundant homologues. [18][19][20] To overcome the drawbacks related to their limited availability, three main strategies have been explored consisting in classically utilizing very active molecular catalysts (at very low concentration), [21][22][23][24][25][26][27][28][29] or in maximizing the number of accessible active sites in properly designed heterogenized [8,[30][31][32][33][34][35] and heterogeneous [17,[36][37][38][39][40][41] catalysts, according to the 'noble metal atom economy' principle. [8] The preparation of supported catalysts can be particularly convenient in this respect.…”
Section: Introductionmentioning
confidence: 99%